Pelayanan Masyarakat dalam Digitalisasi Desa Rayunggumuk UMKM melalui Pembuatan Banner UMKM dan Pendaftaran Lokasi UMKM di Google Maps - Sulis Tiyawati; Lisa Oktavia Anggraini; Muhammad Sulton; Ilham Basri K.; Mas'adah Mas'adah (Fakultas Ekonomi dan Bisnis Islam, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in sustaining rural economies by creating employment opportunities, utilizing local resources, and supporting household income. However, many rural MSMEs continue to face structural challenges, particularly limited promotional capacity and low digital technology adoption, which reduce business visibility, restrict market access, and weaken competitiveness amid increasing economic digitalization. In Rayunggumuk Village, most MSMEs operate informally, rely on word-of-mouth promotion, lack clear visual business identities, and have not utilized digital platforms for business promotion. This community service program aimed to address these issues through simple, low-cost, and context-appropriate promotional strategies by integrating offline visual branding with basic digitalization. Using the Asset-Based Community Development (ABCD) framework, the program involved ten MSMEs from sectors such as processed food, traditional beverages, handicrafts, and local services. The interventions included designing and installing promotional banners and registering business locations on Google Maps, supported by direct mentoring activities. The results showed improved MSME visibility, accessibility, consumer trust, and digital literacy, demonstrating that combining visual branding with digital mapping can effectively support sustainable rural MSME empowerment.